The Interface between Catalytic and Hemopexin Domains in Matrix Metalloproteinase-1 Conceals a Collagen Binding Exosite - Arnold, Laurence H. (American Society for Biochemistry and Molecular Biology, 2011)
Matrix metalloproteinase-1 (MMP-1) is an instigator of collagenolysis, the catabolism of triple helical collagen. Previous studies have implicated its hemopexin (HPX) domain in binding and possibly destabilizing the collagen substrate in preparation for hydrolysis of the polypeptide backbone by the catalytic (CAT) domain. Here, we use biophysical methods to study the complex formed between the MMP-1 HPX domain and a synthetic triple helical peptide (THP) that encompasses the MMP-1 cleavage site of the collagen α1(I) chain. The two components interact with 1:1 stoichiometry and micromolar affinity via a binding site within blades 1 and 2 of the four-bladed HPX domain propeller. Subsequent site-directed mutagenesis and assay implicates blade 1 residues Phe(301), Val(319), and Asp(338) in collagen binding. Intriguingly, Phe(301) is partially masked by the CAT domain in the crystal structure of full-length MMP-1 implying that transient separation of the domains is important in collagen recognition. However, mutation of this residue in the intact enzyme disrupts the CAT-HPX interface resulting in a drastic decrease in binding activity. Thus, a balanced equilibrium between these compact and dislocated states may be an essential feature of MMP-1 collagenase activity.